Participatory design in refugee camps: comparison of different methods and visualization tools. Issue 2 (17th February 2021) - Albadra, Dima; Elamin, Z.; Adeyeye, K.; Polychronaki, E.; Coley, D. A.; Holley, J.; Copping, A.
ABSTRACT: Shelters for the displaced can suffer from socio-cultural incompatibility and significant levels of occupant dissatisfaction. Participatory design (PD) is known to help reduce such issues. This is the first study to investigate the effectiveness of different PD methods at engaging and capturing users' needs for shelter design in refugee camps. It also aimed to identify which visualization tools are best at: engaging participants; communicating designs (e.g. concept, size and materials); and facilitating proposing modifications. This is a particularly large study with 16 workshops and 161 participants. Two PD methods were deployed: (i) design-your-own (where refugees proposed their ideal shelter); (ii) adapt-a-design (where refugees evaluated and modified pre-existing shelter designs). The shelters in (ii) were presented using three visualization tools: computer models, physical prototypes and virtual reality. Design-your-own proved less engaging and led participants to produce designs similar to their existing shelters. Adapt-a-design stimulated more dialogue and was more informative. Physical prototypes facilitated engagement in shelter modifications, computer models proved least able to communicate concepts, while virtual reality was best at communicating scale and size.